Evaluation of Reservoir Capacity and Reliability for Urban Water Utilization in Dili, Timor Leste - Aderita Mariana Takeleb; Joko Sujono; Rachmad Jayadi (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2021)
The ability to store and distribute water resources is very significant to human activities. Therefore, high importance is placed on the sector to address any adverse impact in the event of major shortfall, particularly in Dili, Timor Leste. A study on the development of effective water resource management mechanisms has been conducted to support government visions. As a consequence, priority strategy was initiated to design the necessary infrastructure, in order to match urban demands. One action plan of this effort is by building reservoirs. The purpose of this study was to evaluate the construction of a minor or large reservoir to meet water consumption rate in Dili. Also, the strategy implementation proposal of the reservoir development in Beemos and Becora rivers was prepared by analyzing the reliability and capacity, using a model known as water release standard operating rules. However, water balance simulation results showed the reliability of clean water services from these two small storage units is unable to approach 100%, due to limited volume. The capacity optimization outcomes of large Beemos reservoir indicated the inflow potential at 90% utilization, and therefore is able to balance the urban water demand up to 2030. Despite impressive simulation results, the government is expected to consistently conduct a detailed feasibility study in the upstream area, prior to implementation. Furthermore, large reservoir construction is highly recommended for effective water resource expansion, in an attempt to match the high consumption rate in Dili. This effort possibly supports Timor Leste's targets and sustainable development goals concerning clean water and sanitation.